1978
DOI: 10.1172/jci109053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucagon Deficiency in the Houssay Phenomenon of Dogs

Abstract: A B S T R A C T Plasma glucose, immunoreactive glucagon (IRG), and insulin were measured in hypophysectomized dogs receiving cortisol and thyroid replacement therapy. 4 wk after hypophysectomy mean fasting plasma glucose levels had declined from 90+2 mg/100 ml to 64+2; fasting and arginine-stimulated insulin and IRG levels were, respectively, -50% lower and unchanged. 12 wk or more after hypophysectomy, despite lower plasma glucose levels, fasting and arginine-stimulated IRG levels were significantly below con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…February1980 The present findings showed that the elevated plasma glucose level and gut GI due to pancreatectomy fell down significantly in almost parallel with each other after hypophysectomy. These results were in agreement with the report of Nakabayashi et al(1978).…”
Section: Discussionsupporting
confidence: 94%
“…February1980 The present findings showed that the elevated plasma glucose level and gut GI due to pancreatectomy fell down significantly in almost parallel with each other after hypophysectomy. These results were in agreement with the report of Nakabayashi et al(1978).…”
Section: Discussionsupporting
confidence: 94%
“…However, in the 1970s, several groups reported measurable glucagon levels in insulin-deprived, totally pancreatectomized humans and animals (62-65). The stomach was found to be an important source of the nonpancreatic hyperglucagonemia, and classical α cells were found in the gastric fundus and duodenum of animals and humans (66,67). Gastric α cells were shown to oversecrete glucagon during insulin deficiency and to be more sensitive than pancreatic α cells to small amounts of insulin.…”
Section: Glucagon Sine Qua Non Of Hyperglycemia In All Forms Of Insumentioning
confidence: 99%
“…These insights invalidated the only argument against an essential diabetogenic role for glucagon (67). Glucagonocentrism had become plausible.…”
Section: Glucagon Sine Qua Non Of Hyperglycemia In All Forms Of Insumentioning
confidence: 99%
“…11 Hypophysectomized dogs have decreased postabsorptive insulin concentrations 1213 and suppressed basal and arginine-stimulated plasma glucagon levels. 14 Furthermore, hypophysectomy reduces hepatic glucose production and peripheral glucose uptake. 15 Since treatment of such hypophysectomized dogs with growth hormone or cortisol restores normal glucose turnover rates, 1617 it is not inconceivable that the lack of these hormones together with reduced plasma glucagon levels could be responsible for the decreased glucose production seen after hypophysectomy in normal dogs.…”
mentioning
confidence: 99%
“…1214 In these dogs totally devoid of insulin, hypophysectomy decreased basal and argininestimulated secretion of extrapancreatic glucagon 14 and prevented ketoacidosis, but rarely normalized the hyperglycemia. Amelioration of the diabetic state was probably due to at least three factors: lack of pituitary hormones and reduction of adrenocortical hormones and glucagon in plasma.…”
mentioning
confidence: 99%